Recursive Ant Colony Optimization for Congestion Control in Network - S.RadhaRammohan, Dr.; S.V.Tresa Sangeetha, Dr. (International Journal of Engineering and Technology, 2018)
Nowadays network traffic is large in number, due to large traffic congestion occurs ,even through many congestion avoiding methodology ,to avoid congestion avoidance a new methodology is tried outÂ with the support ofÂ recursive ant colony optimization, which will enhance a pathway to transfer the packets inÂ high congestion conditions by identifying pathway which has less traffic, by that congestion can be eased in high traffic conditions , and delivery speed can also be improved.Â Â Â